Processing and characterization of flame-retardant natural fibre-reinforced epoxy composites and construction of selection charts for engineering applications - Noha Ramadan; Mohamed Taha; Ahmed Elsabbagh (eXPRESS Polymer Letters)
Natural fibre-reinforced polymer composite (NFRPC) has been introduced as one of the solutions to overcome the ecological and environmental problems accompanying the widespread usage of polymeric materials in every facet of life. However, the organic nature of both natural fibres (NFs) and polymers increases their flammability behaviour, and this, in turn, limits their application. In this regard, this work concentrates on studying the effect of adding flame retardants (FR) to jute-reinforced epoxy composites (JRECs), either by treating the jute fabric with diammonium phosphate (DAP) or adding DAP powder to the epoxy resin matrix on the flame retardancy performance as well as the mechanical properties. The results showed that the effect of the incorporation method of DAP either to jute fabric or to resin matrix has a significant difference on the flammability test results at low concentrations; however, at higher concentrations, the flame retardancy performance is not affected by the technique of adding FR to the composite system. On the other hand, the mechanical properties are significantly affected by the method of incorporating FR to JRECs at all concentrations. Moreover, the results obtained from JRECs with FR systems were evaluated and compared with the literature by constructing selection charts that relate the flame retardancy level to mechanical properties.